PERSEPSI MASYARAKAT TENTANG TRADISI A'LAMMANG DI DESA LANTANG, KECAMATAN POLOMBANGKENG SELATAN, KABUPATEN TAKALAR - Riadi S, Moh Ryan; Syarif, Erman; Leo, M Nur Zakaria (LaGeografia, 2019)
This research is A qualitative research aimed intends to understand the phenomena about what is experienced by research subjects that aim to determine people's perceptions of the A?lammang  Tradition and know the efforts made by the Government and the community to preserve the A?lammang  tradition. The A?lammang  tradition is a tradition carried out by the community in Lantang Village, Polombangkeng Selatan District, Takalar Regency, the implementation of which is on Friday, the first week after the rice harvest. The A?lammang  tradition is a form of gratitude for the people in Lantang Village for the rice harvest they have obtained. The tradition that only exists in Lantang Village originates from the existence of deep rivers and the water never dries in the dry and rainy seasons, so the village near the river is named Lantang. After conducting research, it can be concluded that the Government considers the A?lammang  Tradition as a cultural asset in the Lantang Village, with the existence of this tradition will make the Lantang village better known to the outside community and will preserve the A?lammang  Tradition as a cultural asset in the Lantang village.